ANALISIS USAHA PEREMPUAN PEMECAH BATU DAN KONTRIBUSINYA TERHADAP PEMENUHAN KEBUTUHAN KELUARGA DI DESA REBUG KECAMATAN KEMIRI KABUPATEN PURWOREJO - Aris Sulistyanto (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2014)
Efforts to break up the stone is one of the small businesses in the village district of Purworejo Rebug Pecan, the business is dominated by women. Efforts to break this rock is sideline committed by the women so that the income from the business is able to contribute to the fulfillment of the needs of the family.Given the large and its benefits will attempt this rude made by women in order to contribute to meeting the needs of everyday life. The issues examined in this study are: (1) how does the effort women-breaking stones in the village of Rebug Pecan Purworejo District?. (2) how to income level and household needs the stone-breaking women?. (3) How women business constraints solvers stones in the village of Rebug and how such constraints facing solutions?. (4) how large a contribution given to women in the villages of stone breakers Rebug village subdistrict Kemiri Regency Purworejo towards the fulfillment of the needs of the family?.the data using the method of question form, interview and documentation. The Data collected in this study Population is the whole of the women in the village of Solver Rebug Pecan Purworejo District as much as 37 women rock breakers). The collection is analyzed by the method of analysis tools contribute a percentage of the revenue.The conclusions of this study are: (1) as seen from the results of the research the average income levels of women’s efforts to break up the rock in Purworejo District Rebug Pecan is amounting to Rp 360.135; 00. The highest income amounting to Rp 500,000; 00 and lowest income amounting to Rp 300,000; 00. (2) based on an analysis of the percentage of the contribution revenues against stone-breaking women’s fulfillment needs of families earned income of women as the stone-breaking effect on income total household registration 39,45%. (3) based on an analysis of the percentage of the contribution revenues against stone-breaking women’s fulfillment needs of families earned income of women as the stone-breaking effect on the average cost of fulfilling the needs of the household registration of 50,70%.(4) based on the results of the study the main barriers facing women stone breaker was hot and heavy weight stone while holding the other obstacle is, itching, could not work optimally when the rainy season floods or, marketing issues, the price of a low stone fragments do not comply with what they are doing.